Tecnicas de protoplastização e isolamento de DNA de alto peso molecular de aspergillus niger - Borges, Maria Inês, 1954- (1987)
Orientadores: Renato Bonatelli Junior, Maristela O. Azevedo, Maria Sueli S. Felipe